A comparison of verb and noun retrieval in Mandarin–English bilinguals with English-speaking monolinguals. Issue 5 (November 2019) - LI, RAN; FAROQI-SHAH, YASMEEN; WANG, MIN
Abstract : The finding that noun production is slower and less accurate in bilinguals compared to monolinguals is well replicated, but not well understood. This study examined the two prominent theoretical accounts for this bilingual effect: weaker links and cross-language interference. Highly proficient Mandarin–English bilinguals and English-speaking monolinguals named pictures in which the effects of grammatical class, word frequency and translatability were examined. While bilinguals were slower overall than monolinguals in both L1 and L2, the magnitude of this bilingual effect was smaller for verbs than for nouns. Bilinguals showed a larger production advantage for high vs. low frequency words in their L2 relative to monolinguals and their L1. Bilinguals also showed an advantage for words with greater translatability, which did not differ across grammatical categories. The findings lend partial support to the weaker links account, and reveal cross-language facilitation rather than interference.